APPLICATION OF DIGITAL PLATFORMS IN THE STATISTICAL SYSTEM BASED ON INTERNATIONAL EXPERIENCE - Mustafakulov O'ktam Ungboyevich (European Science Publishing, 2024)
This article covers the international experimental application of digital platforms in the statistical system. Scientific-based proposals and recommendations have been developed on issues of development of the organization of digital platforms in the statistical system, problems in organizing statistical activities through digital platforms, ways of introducing modern technologies into it, further improvement of the activities of regional statistical departments on the basis of digital platforms. The article also covers the issues of developing the organization of work with data on the basis of digital technologies in the statistical system, analyzes the existing problems in this area, studies the factors that hinder the processes of digitization and describes the directions of digitization of production.
Keywords: Statistics, statistical system, digital platform, digitization of the economy, Digital Economy, Network, Technology, Information, Communication, Platform, analysis.